EFEKTIVITAS PERSILANGAN IKAN MOLLY BALON SUNKIST (Poecilia sphenops) DENGAN MOLLY MARBLE (Poecilia sphenops) TERHADAP VARIASI WARNA - Setiawan, Joni; Hartono, Dwi Puji; Marlina, Eulis (Jurnal Perikanan Terapan, 2024)
The Marble Molly fish (Poecilia sphenops) and the Sunkist Balloon Molly (Poecilia sphenops) are one of the fish that are popular in Indonesia. It is hoped that crossing sunkist mollies and marble mollies will produce unique colors and new patterns, with diverse and unique colors so that public interest will once again be high in keeping ornamental fish, especially mollies. The methods used start from preparing tools and materials, preparing spawning tanks and larval rearing tanks, selecting mature gonad male and female parents with the characteristics of the male having a gonopodium on his stomach while the female does not have it with the age of the male and female being at least 4 months before they can be spawned. The cross is carried out with a ratio of males and females, namely 5 males and 10 females in each spawning tank, there are 6 spawning tanks with 3 tanks representing the cross between a marbled male and a Sunkis female and another 3 tanks with a Sunkist male and a marbled female, then the best data is taken from the 2nd following treatment. The results obtained were the emergence of 3 color variations and 5 pattern variations with unique and varied colors and patterns.